THE SPIRAL-UP INNOVATION OF PETROCHEMICAL COMPLEX IN GROUP OPERATION CONCERNING THE CASE OF RING (RESEARCH ASSOCIATION OF REFINERY INTEGRATION FOR GROUP-OPERATION) IN JAPAN - Inaba, Kazuya (Revista Administração em Diálogo - RAD, 2010)
The circumstances that surround the oil and petrochemical industry recently have beensevere. Under such a severe competitive situation, oil and petrochemical companies cameup with the idea of business cooperation in the same region in order to acquire globalcompetitiveness. In this paper, the approach and ways of the high-level integration forgroup operation in petrochemical complex are analyzed, the meaning of RING projects isdeclared, and the economy that arises from group operation business is considered.Cooperation with some businesses would be effective for energy conservation andenvironmental measures, and would advance the possibility to achieve economies ofpublic profit. Also, group operation would break the stoppage and promote innovationsone after another in a petrochemical complex.